Toll‐IL1 receptor‐mediated innate immune responses vary across HBV genotype and predict treatment response to pegylated‐IFN in HBeAg‐positive CHB patients. Issue 3 (5th October 2015) - Visvanathan, K.; Lang, T.; Ryan, K.; Wilson, R.; Skinner, N. A.; Thompson, A. J. V.; Ahn, S. H.; Weilert, F.; Abbott, W.; Gane, E.; Colledge, D.; Li, K.; et al.
Summary: Patients with hepatitis B e antigen (HBeAg)‐positive chronic hepatitis B (CHB) have suppressed TLR2 expression, function and cytokine production. The aim of this study was to explore the importance of hepatitis B virus (HBV) genotype in innate immune responses and investigate whether Toll‐like receptor (TLR) expression/function has potential roles as predictive biomarkers of successful therapy with pegylated interferon (Peg‐IFN) therapy of HBeAg seroconversion in HBeAg‐positive patients. We showed that as early as 4 weeks after initiation of Peg‐IFN, future HBeAg seroconverters had significantly elevated levels of TLR2 expression on monocytes. TLR2‐associated IL‐6 production at baseline and week 4 of therapy and TLR4 IL‐6 production at week 4 were also markedly elevated in HBeAg seroconverters. HBV genotype also influenced treatment response, with genotypes A and B more likely to seroconvert than D. We were able to demonstrate that these differences were due in part to the interaction of the specific HBeAg proteins with TLR pathway adaptor molecules, and these interactions were genotype dependent. HBeAg‐mediated modulation of TLR signalling was also observed in Huh7 cells, following stimulation with Pam3Cys. Importantly, the addition of IFN‐α to TLR2‐stimulated cells cotransfected with an HBeAg expression plasmid reversed HBeAg‐mediated suppression of hepatocytes. These findings demonstrate that patients with an activated inflammatory response are much more likely to respond to IFN therapy, with TLR responses showing promise as potential biomarkers of HBeAg seroconversion in this setting. Furthermore, our findings suggest there is differential genotype‐specific HBeAg suppression of innate signalling pathways which may account for some of the clinical differences observed across the CHB spectrum.